Zwitterionic polymer, electrochemical sensor and preparation method and application of zwitterionic polymer
By modifying the electrode surface by zwitterionic polymer and loading silver-copper nanoparticles and thiol aptamers, the problem of electrochemical sensors being adsorbed by interfering substances in actual sample detection is solved, achieving efficient and accurate detection results.
Patent Information
- Application Number
- CN202510083828.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Electrochemical sensors are susceptible to nonspecific adsorption of interfering substances such as proteins, sugar compounds, etc. in actual sample detection, resulting in reduced sensitivity and accuracy. The modification process of existing anti-fouling materials is complex and costly.
Zwitterionic polymers are used to modify the electrode surface, and the anti-fouling layer is formed by photoinduced in situ polymerization, and silver-copper nanoparticles and thiol aptamers are loaded on its surface to improve the anti-fouling performance.
It realizes the reduction of non-specific adsorption during the detection process, improves detection efficiency and accuracy, and reduces the complexity and cost of sample pretreatment.
Smart Images

Figure CN119955014A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical detection, and in particular relates to a zwitterionic polymer, an electrochemical sensor, and a preparation method and application thereof. Background Art
[0002] Compared with traditional detection methods, electrochemical sensors have the advantages of fast analysis speed, high sensitivity, easy operation, easy miniaturization and portability. Therefore, they are often used in the fields of medicine, food safety, etc. for analysis and detection. However, when electrochemical sensors are applied to actual sample detection, interfering substances in the samples, such as proteins and sugar compounds, are easy to interact with the surface of the electrochemical sensor, produce non-specific adsorption, and thus contaminate the sensor, seriously affecting the sensitivity and accuracy of the sensor. Usually, researchers will pre-treat the samples, but this process is time-consuming, complicated to operate, and has low detection efficiency. Therefore, the electrode surface is modified by anti-fouling materials to construct an electrochemical sensor with its own anti-fouling effect. Thereby, samples that have only undergone simple pre-treatment can be sensitively and accurately detected during the detection process, greatly improving the detection efficiency.
[0003] Commonly used antifouling materials modified on the sensor surface include polyethylene glycol (PEG) and its derivatives, zwitterionic materials, and peptides. The above antifouling materials all have strong hydrophilicity and electrical neutrality. The hydrophilic surface formed by their modification can combine with water molecules through electrostatic interactions, hydrogen bonds, etc. to form a dense hydration layer, thereby reducing nonspecific adsorption. PEG and peptides are often used in the preparation of antifouling electrochemical sensors, but PEG is easily oxidized and broken, and peptides are easily enzymatically hydrolyzed when used in biological media and have high costs. Zwitterionic materials are used in electrochemical sensors with the characteristics of stable antifouling, but due to their complex polymerization process, they are difficult to anchor on the sensor surface after synthesis. At present, there are relatively few cases of zwitterionic material modification of sensors. Summary of the invention
[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a zwitterionic polymer. The second purpose of the present invention is to provide a method for preparing the above-mentioned zwitterionic polymer. The third purpose of the present invention is to provide an electrochemical sensor. The fourth purpose of the present invention is to provide a method for preparing the above-mentioned electrochemical sensor. The fifth purpose of the present invention is to provide the application of the above-mentioned electrochemical sensor.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a zwitterionic polymer, wherein the structural formula of the biomimetic zwitterionic polymer is shown in Formula 1 below:
[0007]
[0008] Wherein, x and y are the numbers of each monomer structural unit.
[0009] The second aspect of the present invention provides a method for preparing the zwitterionic polymer of the first aspect, comprising the following steps: subjecting N-[(3-(dimethylamino)propyl]methacrylamide to an oxidation reaction to obtain a zwitterionic monomer, and subjecting the zwitterionic monomer to a photopolymerization reaction with methacrylate sulfobetaine to obtain the zwitterionic polymer.
[0010] Preferably, the oxidation reaction step comprises: reacting N-[(3-(dimethylamino)propyl]methacrylamide with hydrogen peroxide under an oxygen atmosphere.
[0011] More preferably, the oxidation reaction also uses a stabilizer.
[0012] More preferably, the stabilizer is diethylenetriaminepentaacetic acid.
[0013] More preferably, the temperature of the oxidation reaction is 60-70°C.
[0014] More preferably, the oxidation reaction time is 4 to 7 hours.
[0015] More preferably, the oxidation reaction is a reaction of N-[(3-(dimethylamino)propyl]methacrylamide in an aqueous solution of hydrogen peroxide.
[0016] More preferably, the method further comprises: extracting and collecting the water phase after the oxidation reaction, dissolving the water phase in anhydrous ethanol and removing water by rotary evaporation, and freeze-drying to obtain the zwitterionic monomer.
[0017] Preferably, the photopolymerization step comprises: the zwitterionic monomer reacts with methacrylate sulfobetaine under the action of a photoinitiator.
[0018] More preferably, the photoinitiator is selected from at least one of 2-hydroxy-2-methylpropiophenone, 1-hydroxy-cyclohexyl phenyl ketone, and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone.
[0019] More preferably, the photopolymerization reaction is carried out under ultraviolet light.
[0020] More preferably, the reaction time of the photopolymerization reaction is 20 to 40 minutes.
[0021] Preferably, the mass ratio of the zwitterionic monomer to methacrylate sulfobetaine is (1-9):1.
[0022] More preferably, the mass ratio is (3-6):1.
[0023] The third aspect of the present invention provides an electrochemical sensor, comprising an electrode, the surface of the electrode is an anti-fouling layer formed by the zwitterionic polymer described in the first aspect, and the surface of the anti-fouling layer is loaded with silver-copper nanoparticles and thiol aptamers.
[0024] Preferably, the electrode is a glassy carbon electrode.
[0025] Preferably, the thiol aptamer is a thiol chloramphenicol aptamer.
[0026] More preferably, the sequence of the mercaptochloramphenicol aptamer is 5'-SH-(CH2)6-ACT TCA GTG AGT TGTCCC ACG GTC GGC GAG TCG GTG GTAG-3'.
[0027] The fourth aspect of the present invention provides a method for preparing the electrochemical sensor according to the third aspect, comprising the following steps:
[0028] S1, subjecting N-[(3-(dimethylamino)propyl]methacrylamide to an oxidation reaction to obtain a zwitterionic monomer, mixing the zwitterionic monomer, methacrylate sulfobetaine and a photoinitiator in a solvent to obtain a mixed solution, coating the mixed solution on the surface of an electrode, and then subjecting the mixed solution to a photopolymerization reaction to obtain an electrode 1 having an antifouling layer on the surface;
[0029] S2, coating a dispersion containing silver-copper nanoparticles on the surface of the anti-fouling layer, reacting to modify the silver-copper nanoparticles on the surface of the anti-fouling layer to obtain electrode 2; placing electrode 2 in a thiol aptamer solution for incubation to obtain the electrochemical sensor.
[0030] The invention coats zwitterionic monomers and methacrylate sulfobetaine on the electrode surface, and modifies the zwitterionic copolymer on the electrode surface through photoinduced in-situ polymerization to form an antifouling surface. The in-situ synthesis method solves the problem that the zwitterionic material is difficult to anchor on the sensor surface after synthesis.
[0031] Preferably, in step S1, the coating method is drop coating.
[0032] Preferably, in step S1, the photopolymerization reaction is carried out under ultraviolet light.
[0033] Preferably, in step S1, the reaction time of the photopolymerization reaction is 20 to 40 minutes.
[0034] Preferably, step S1 further comprises: after the photopolymerization reaction, immersing the electrode in PBS to remove excess monomers and photoinitiator.
[0035] Preferably, the silver-copper nanoparticles are synthesized by using a seed growth method with silver nanoparticles as a substrate.
[0036] More preferably, the step of preparing the silver nanoparticles comprises: reacting a reducing agent, a ligand and a silver source to obtain silver nanoparticles.
[0037] More preferably, the reducing agent is glucose; the ligand is hexadecylamine; and the silver source is silver nitrate.
[0038] More preferably, the reaction time of the reaction is 50 to 70 minutes; and the reaction temperature is 90 to 120°C.
[0039] More preferably, the preparation step of the silver-copper nanoparticles comprises: reacting trimethylamine, silver nanoparticles and a copper source to obtain silver-copper nanoparticles.
[0040] Preferably, in step S2, a dispersion containing silver-copper nanoparticles is coated on the surface of the anti-fouling layer, and the dispersion is allowed to stand for a period of time for self-assembly reaction to modify the surface of the anti-fouling layer with silver-copper nanoparticles to obtain an electrode 2.
[0041] Preferably, in step S2, the incubation time is 8 to 12 hours; the incubation temperature is 0 to 5°C.
[0042] Preferably, in step S2, the concentration of the thiol aptamer solution is 0.1 to 3 μmol L -1
[0043] The fifth aspect of the present invention provides use of the electrochemical sensor described in the third aspect in detecting chloramphenicol.
[0044] Preferably, the method for detecting chloramphenicol comprises the following steps:
[0045] Prepare chloramphenicol standard solutions of different concentrations, and use the electrochemical sensor described in the third aspect for detection, scan with differential pulse voltammetry (DPV), calculate the signal suppression rate by recording the current signal before and after the detection, and draw a standard curve based on the obtained signal suppression rates of different concentrations and the concentration of the chloramphenicol standard solution; use the above-mentioned electrochemical sensor to collect and detect the sample liquid to be tested, determine whether the sample liquid to be tested contains chloramphenicol by analyzing the current signals before and after the detection, and compare the obtained signal suppression rate with the standard curve to obtain the concentration of chloramphenicol in the sample liquid to be tested.
[0046] Preferably, the electrochemical sensor is used in detecting chloramphenicol residues in food.
[0047] More preferably, the method for detecting chloramphenicol residue in food comprises the following steps:
[0048] The food sample after simple treatment is diluted to a certain multiple to obtain a sample liquid to be tested; the electrochemical sensor is used to collect and detect the sample liquid to be tested, and the current signal before and after the detection is analyzed to determine whether the sample liquid to be tested contains chloramphenicol, and the obtained signal inhibition rate is compared with the standard curve to obtain the concentration of chloramphenicol in the sample liquid to be tested.
[0049] The beneficial effects of the present invention are:
[0050] The present invention provides a zwitterionic polymer, which is a sulfobetaine type zwitterionic polymer, has strong hydrophilicity and electrical neutrality, and the solvation effect and hydrogen bonding effect of the charged functional groups can form a hydration layer on the surface of the zwitterionic polymer. The surface of the hydration layer can effectively resist nonspecific adsorption, has high anti-fouling performance, and has great application potential in the field of anti-fouling electrochemical sensors.
[0051] Specifically, compared with the prior art, the present invention also has the following advantages:
[0052] (1) The present invention also provides an electrochemical sensor. The anti-fouling layer formed by the zwitterionic polymer on the electrochemical sensor can effectively resist nonspecific adsorption, has high anti-fouling performance, and can reduce and eliminate signal interference in the detection of actual samples, thereby reducing the sample pre-treatment work; in addition, the silver-copper nanoparticles (Ag-CuNDs) on the electrochemical sensor can not only be used for the connection of thiol aptamers but also enhance the electrochemical signal, and the loaded silver-copper nanoparticles do not affect the anti-fouling performance of the zwitterionic polymer.
[0053] (2) The electrochemical sensor of the present invention can be used for chloramphenicol electrochemical aptamer sensor. Due to the high selectivity of the mercaptochloramphenicol aptamer, the chloramphenicol electrochemical aptamer sensor has specific selectivity and high sensitivity to chloramphenicol within a certain range. In addition, the zwitterionic polymer can make the electrochemical sensor have the characteristics of high anti-interference ability and good reproducibility in the detection of chloramphenicol residues in food. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Schematic diagram of the construction of anti-fouling electrochemical sensor;
[0055] Figure 2 H NMR spectra of DMAPMA (a), TMAOMA (b), and PTMAO-SBMA (c);
[0056] Figure 3 Characterization of Ag-Cu NDs, including transmission electron microscopy (a), energy dispersive X-ray spectroscopy (b) and ultraviolet absorption spectrum (c);
[0057] Figure 4 Scanning electron microscopy (SEM) images of different modified electrodes: GCE (a), PTMAO-SBMA / GCE (b) and Ag-Cu NDs / PTMAO-SBMA / GCE (c)
[0058] Figure 5 Optimization of the ratio of zwitterionic monomers, (a) bovine serum albumin (BSA), (b) lysozyme (Lys), (c) glycogen (Gn);
[0059] Figure 6 Concentration optimization of Ag-Cu NDs (a) and aptamer (b);
[0060] Figure 7 Comparison of signal inhibition rates of GCE, PTMAO-SBMA / GCE, and Ag-Cu NDs / PTMAO-SBMA / GCE at different concentrations of (a) glucose, (b) fructose, and (c) glycogen;
[0061] Figure 8 DPV signal responses of GCE in (a) glucose, (b) fructose and (c) glycogen;
[0062] Fig. 9 DPV signal responses of PTMAO-SBMA / GCE in (a) glucose, (b) fructose, and (c) glycogen;
[0063] Fig.10 DPV signal responses of Ag-Cu NDs / PTMAO-SBMA / GCE in (a) glucose, (b) fructose, and (c) glycogen.
[0064] Fig.11 For GCE, PTMAO-SBMA / GCE, Ag-Cu NDs / PTMAO-SBMA / GCE in 10 mg mL -1 The signal inhibition rate of glucose, fructose and glycogen solutions;
[0065] Fig.12 The DPV response signals of the antifouling electrochemical sensor combined with different concentrations of chloramphenicol;
[0066] Fig.13 is the relationship curve between chloramphenicol concentration and signal inhibition rate; the inset shows the corresponding standard curve;
[0067] Fig.14 DPV response of the preparation process of antifouling electrochemical sensor;
[0068] Fig.15(a) Specificity test results, (b) repeatability test results, and (c) stability test results of the anti-fouling electrochemical sensor. DETAILED DESCRIPTION
[0069] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0070] The information of the raw materials and reagents used in the examples and experimental analysis of the present invention is as follows:
[0071] 2-Hydroxy-2-methylpropiophenone, copper(I) acetate (CuOAc), diethylenetriaminepentaacetic acid, N-(3-dimethylaminopropyl)methacrylamide (DMAPMA), glycogen (Gn) were purchased from Roan's reagent; bovine serum albumin (BSA) was purchased from Beijing Solebow Technology Co., Ltd.; hydrogen peroxide (H2O2, 30%), dichloromethane (DCM), anhydrous ethanol were purchased from Tianjin Damao Chemical Reagent Company; lysozyme (Lys) was purchased from Boster Biotechnology; fluorescein isothiocyanate labeled bovine serum albumin (FITC-BSA) was purchased from Beijing Zhongke Chenyu Technology Co., Ltd.; potassium ferrocyanide trihydrate (K4Fe(CN)6·3H2O), potassium ferrocyanide (K3Fe(CN)6), potassium chloride (KCl), sodium dihydrogen phosphate dihydrate (Na H2PO4·2H2O), sodium phosphate dodecahydrate (Na2HPO4·12H2O), L-(+) ascorbic acid (99%), and sodium chloride (NaCl) were purchased from Sinopharm Group; chloramphenicol aptamer was purchased from Shanghai Shenggong Biotechnology; D-(+)-glucose (Glu), D-fructose (Fru), and α-lactose (Lac) were purchased from Shanghai Blue Season Technology Co., Ltd.; chloramphenicol (CAP), tetracycline hydrochloride (TET), ofloxacin (OFLX), kanamycin sulfate (KANA), amoxicillin (AMX), tris(2-carboxyethyl)phosphine hydrochloride (TCEP), and 2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (SBMA) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; ultrapure water (18.2 MΩcm -1 )Made in the laboratory.
[0072] Example 1
[0073] This embodiment provides an electrochemical sensor, and a schematic diagram of its preparation method is shown in FIG. Figure 1 As shown, the preparation process is specifically as follows:
[0074] (1) The synthesis equation of zwitterionic monomer (TMAOMA) is as follows:
[0075]
[0076] The specific preparation process is as follows: In a three-necked round-bottom flask, diethylenetriaminepentaacetic acid (80 mg) is dissolved in 30 mL of deionized water under vigorous stirring. Then hydrogen peroxide (30% solution, 4.78 g) is slowly added to the flask, and the mixed solution is heated to 60°C and purged with oxygen. DMAPMA (15 g) is dissolved in 10 mL of deionized water and slowly added to the flask. The temperature is raised to 65°C, and the reaction time is 5 h. After the solution is naturally cooled to room temperature, it is extracted with DCM several times and the aqueous phase is collected. The collected aqueous phase is dissolved in anhydrous ethanol and most of the water is removed by a rotary evaporator, and the yellow-white waxy substance is obtained by freeze-drying for 24 h.
[0077] The hydrogen nuclear magnetic resonance spectra of TMAOMA and DMAPMA are as follows: Figure 2 As shown, it can be proved that the target product is synthesized.
[0078] (2) Preparation of zwitterionic copolymer antifouling interface on electrode surface: polish glassy carbon electrode (GCE) with alumina powder, then ultrasonically clean with ultrapure water and anhydrous ethanol, and blow dry with high-purity nitrogen to obtain a clean glassy carbon electrode. Prepare TMAOMA in step (1) to a concentration of 200 mg mL -1 TMAOMA aqueous solution; sulfobetaine (SBMA) was prepared to a concentration of 200 mg mL -1 SBMA aqueous solution; TMAOMA solution and SBMA solution were mixed according to volume ratios of 10:0, 9:1, 8:2, and 7:3, and a photoinitiator (2-hydroxy-2-methylpropiophenone) with a mass ratio of 0.1% was added to obtain a mixed solution. 5 μL of the mixed solution was dripped onto the electrode surface, and a 365 nm light-induced in-situ reaction was performed for 30 min to polymerize and synthesize a series of PTMAO-SBMA copolymers. The copolymers formed were named PTMAO-SBMA0, PTMAO-SBMA1, PTMAO-SBMA2, and PTMAO-SBMA3. Then, it was immersed in PBS (10 mmol L -1 ) solution to allow it to fully swell and remove excess monomers, thereby obtaining an electrode with a stably modified anti-fouling sensing interface, which is denoted as PTMAO-SBMA / GCE.
[0079] The polymerization equation of TMAOMA and SBMA is:
[0080]
[0081] The hydrogen nuclear magnetic resonance spectrum of PTMAO-SBMA is as follows Figure 2 As shown, it can be proved that the target product is synthesized.
[0082] (3) Preparation of silver-copper nanoparticles and their loading on electrodes:
[0083] Preparation of Ag-Cu NDs: 0.045 g hexadecylamine, 3.43 mL water, 1.2 mL silver nitrate (100 m mol L -1 ) and 0.37 mL of glucose (1 M) were added to a 40 mL pressure bottle in sequence. After magnetic stirring for 5 h, the mixture was heated in a 100 °C oil bath for 1 h. The pressure bottle was then taken out and cooled naturally. It was washed with ultrapure water and centrifuged 2-3 times (13300 rpm, 10 min), and directly redispersed in 9 mL of ultrapure water for inoculation growth of Ag-Cu NDs.
[0084] 0.3 g trimethylamine, 0.3 mL anhydrous copper acetate (100 mmol L -1 ), 8.9 mL of ultrapure water and 200 μL of an aqueous solution of silver nanoparticles (Ag NPs) were added to a 40 mL pressure bottle in sequence. The resulting mixture was stirred for 5 hours, and then 0.6 mL of ascorbic acid (1 mol L -1 ) and stirred for 10 minutes. The pressure bottle was placed in an oil bath at 150°C and heated for 12.5 minutes. It was washed with ultrapure water and centrifuged 3-5 times (13300 rpm, 10 minutes), and concentrated to 10 mL for later use (the concentration of Ag-Cu NDs was defined as 1×).
[0085] Figure 3 For the characterization of Ag-Cu NDs, Figure 3 a in the figure is transmission electron microscopy (TEM), Figure 3 b in the equation is the energy dispersive X-ray spectrum, Figure 3 In figure c is the ultraviolet absorption spectrum.
[0086] Figure 3 The synthesized Ag-Cu NDs were fully characterized by TEM, EDX, UV-visible spectroscopy and TEM images of Ag-Cu NDs ( Figure 3 In a), a gourd-like nanostructure consisting of two hemispherical domains was observed. The size of each domain ranged from 25–35 nm. EDX elemental map ( Figure 3 b) Confirms the existence of separated Ag and Cu domains in the nanocrystals, where the Ag domain is yellow and the Cu domain is red. In addition, the unique structural features of Ag-Cu NDs are also reflected in the optical properties. As shown in the UV-visible spectrum ( Figure 3c) Two peaks appeared at ~409nm and ~585.5nm, which were blue-shifted by ~6.5nm relative to the peak at Ag NPs (~415.5nm). Since the size and shape of Ag NPs remained unchanged during the seed growth of Ag-Cu NDs, the blue shift of the Ag NPs peak may indicate that there is charge transfer between the Cu domain and the Ag domain. In summary, the characterization results confirmed that Ag-Cu NDs nanocrystals were successfully synthesized in this example.
[0087] Ag-Cu NDs solutions with concentrations of 1×, 2×, 3×, 4×, and 5× were drop-coated on the prepared antifouling sensing interface PTMAO-SBMA / GCE surface, respectively. After being placed at room temperature for 30 min, the Ag-Cu NDs that were not firmly bound were rinsed with ultrapure water to obtain an electrode with stably modified antifouling sensing interface and silver-copper nanoparticles, which was recorded as Ag-Cu NDs / PTMAO-SBMA / GCE.
[0088] (4) At 4°C, Ag-Cu NDs / PTMAO-SBMA / GCE were placed in the presence of 0.05, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.1 μmol L -1 , incubated in 200 μL of chloramphenicol aptamer solution for 10 h, the sequence of the chloramphenicol aptamer is 5'-SH-(CH2)6-ACT TCA GTG AGT TGT CCC ACG GTC GGC GAG TCG GTG GTAG-3', and a working electrode modified with the aptamer can be obtained, which is recorded as Apt-Ag-Cu NDs / PTMAO-SBMA / GCE.
[0089] Figure 4 Scanning electron microscope (SEM) images of different modified electrodes.
[0090] Figure 4 a shows that the surface of the polished GCE is flat and smooth. When the zwitterionic copolymer (PTMAO-SBMA) is formed by in-situ polymerization on its surface ( Figure 4 b). It can be seen that the surface of GCE becomes rough and the zwitterionic copolymer is evenly distributed on its surface in a dot-like manner. The strong adhesion between polyacrylic acid and GCE is the result of a large number of synergistic interactions, including cation-π interaction, electrostatic attraction, and mechanical interlocking structure. When Ag-Cu NDs ( Figure 4 c) It can be seen that finer spherical particles are evenly distributed.
[0091] Comparative Example 1
[0092] This comparative example provides an electrochemical sensor, and the specific preparation process is as follows:
[0093] The preparation method of Ag-Cu NDs solution is the same as that of Example 1;
[0094] The Ag-Cu NDs solution with a concentration of 4× was drop-coated on the prepared anti-fouling sensing interface PTMAO-SBMA / GCE surface. After being placed at room temperature for 30 minutes, the unbound Ag-Cu NDs were rinsed with ultrapure water to obtain an electrode stably modified with silver-copper nanoparticles, which was recorded as Ag-Cu NDs / GCE.
[0095] Ag-Cu NDs / PTMAO-SBMA / GCE were placed in a 0.5 μmol L -1 , incubated in 200 μL of chloramphenicol aptamer solution for 10 h, the sequence of the chloramphenicol aptamer is 5'-SH-(CH2)6-ACT TCA GTG AGTTGT CCC ACG GTC GGC GAG TCG GTG GTAG-3', and a working electrode modified by the aptamer can be obtained, which is recorded as Apt-Ag-Cu NDsGCE.
[0096] Detection experiment
[0097] 1. The electrode system used in the present invention is based on the traditional three-electrode system: a glassy carbon electrode is used as a working electrode; a platinum electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode.
[0098] The electrochemical experiments were all carried out on an IVIUM electrochemical workstation.
[0099] All electrochemical tests were performed in an electrochemical probe solution containing 5 mmol L - 1 K3[Fe(CN)6] / K4[Fe(CN)6] and 0.2mol L -1 Preparation of PBS: Accurately weigh 35.8 g of disodium hydrogen phosphate (Na2HPO4·12H2O) and 15.6 g of sodium dihydrogen phosphate (NaH2PO4·2H2O), place in a 500 mL volumetric flask, and dilute with ultrapure water to obtain 0.2 mol L -1 Na2HPO4 solution and 0.2 mol L -1 NaH2PO4 solution. Use a measuring cylinder to measure 324 mL of 0.2 M Na2HPO4 solution and 0.2 mol L -1 76 mL of NaH2PO4 solution, then add 3.6 g of sodium chloride solid (NaCl), mix well, and obtain 0.2 mol L -1PBS solution was placed at room temperature. Preparation of electrochemical probe solution (K3[Fe(CN)6] / K4[Fe(CN)6]): Accurately weigh 164.62 mg of potassium ferrocyanide (K3[Fe(CN)6]), 184.17 mg of potassium ferrocyanide (K4[Fe(CN)6]) and 1491.02 mg of potassium chloride (KCl). -1 Dilute the pH 7.4 PBS solution to 0.01 mol / L -1 Then, 0.01 mol L -1 The above drugs were dissolved in PBS solution with pH 7.4 as solvent, and finally the volume was fixed in a 100 mL volumetric flask to obtain a bright yellow solution, that is, 5 mmol L -1 The electrochemical probe K3[Fe(CN)6] / K4[Fe(CN)6], containing 0.2 mol / L KCl) solution, was wrapped in tin foil and stored in a 4°C refrigerator until use.
[0100] In the present invention, differential pulse voltammetry (DPV) was used to record the current response value of the modified electrode before and after incubation (the electric signal before incubation was I0, and the electric signal after incubation was I). The potential range of the differential pulse voltammetry was -0.2V to 0.6V, the amplitude was 10mV, and the scanning rate was 50mV S -1 The electrical signal change value (△I=I0–I) and electrical signal suppression rate (Signal Suppression(%)=[(I0–I) / I0]×100) were calculated using these values.
[0101] 2. The prepared zwitterionic copolymer antifouling interface electrodes PTMAO-SBMA0 / GCE, PTMAO-SBMA1 / GCE, PTMAO-SBMA2 / GCE, PTMAO-SBMA3 / GCE and GCE were immersed in 1.0 and 10.0 mg mL -1 of bovine serum albumin (BSA), lysozyme (Lys), and 10.0 and 50.0 mg mL -1 Incubate in lactose (Lac) solution for 30 min. Immerse the working electrode to be tested in the electrochemical probe solution, scan with DPV in the potential range of -0.2V-0.6V, record the current response value before and after incubation to obtain the signal inhibition rate, and then more intuitively compare the anti-fouling ability of the anti-fouling sensing interface of zwitterionic copolymers with different proportions. Figure 5 From a, b, and c, it can be concluded that the signal suppression rate of PTMAO-SBMA2 / GCE is always the lowest, indicating that it has the best anti-fouling ability and will be used in the subsequent construction of anti-fouling electrochemical sensors.
[0102] 3. The working electrodes Ag-Cu NDs / PTMAO-SBMA / GCE modified with different concentrations of Ag-Cu NDs and the working electrodes Apt-Ag-Cu NDs / PTMAO-SBMA / GCE modified with different concentrations of aptamers were immersed in the electrochemical probe solution, and DPV scanning was performed in the potential range of -0.2V-0.6V. The current response values before and after incubation were recorded to obtain the signal inhibition rate. Figure 6 It can be concluded that the concentration of 4× Ag-Cu NDs solution and 0.5 μmol L -1 The electrode prepared by aptamer solution has the best performance.
[0103] 4. Based on the actual samples tested in the subsequent tests, which were honey and pig liver samples with simple pretreatment, the main components that are prone to nonspecific adsorption are glucose (Glu), fructose (Fru), and glycogen (Gn). -1 of glucose and fructose and 0.1, 1, 10 mg mL -1 The glycogen solution was taken as a contaminant. It is worth noting that the glycogen concentration of the pig liver sample solution after simple pretreatment was much lower than 0.1 mg mL -1 The bare GCE, zwitterionic copolymer antifouling sensing interface and the antifouling sensing interface modified with Ag-Cu NDs were immersed in the above-mentioned concentrations of glucose, fructose and glycogen solutions and incubated for 30 minutes. The working electrode to be detected was immersed in the electrochemical probe solution and scanned by DPV in the potential range of -0.2V-0.6V. The DPV signal responses of different modified electrodes GCE, PTMAO-SBMA / GCE, and Ag-Cu NDs / PTMAO-SBMA / GCE in different pollutants are shown in the following figure. Figure 8-10 The signal inhibition rate was calculated by recording the current response values before and after incubation. Figure 7 It can be concluded that even at 50 mg mL -1 Glucose, fructose, 10mg mL -1 In the glycogen solution, the signal inhibition rate of PTMAO-SBMA / GCE was as low as 1.61%, 1.91%, and 7.08%, which was much lower than the signal inhibition rate of GCE (42.08%, 52.81%, and 65.58%). In addition, it can be clearly seen that when the antifouling surface is loaded with Ag-Cu NDs (Ag-Cu NDs / PTMAO-SBMA / GCE), its antifouling effect is not affected.
[0104] Dissolve GCE, Ag-Cu NDs / GCE, PTMAO-SBMA / GCE, Ag-Cu NDs / PTMAO-SBMA / GCE in 10 mg mL -1After incubation in glucose, fructose and glycogen solutions for 30 minutes, the results showed that the signal suppression rate of Ag-Cu NDs / GCE was not much different from that of GCE, proving that it is easily interfered by interferences, resulting in inaccurate test results. Therefore, Ag-Cu NDs / GCE cannot be used for detection in samples with simple pretreatment. The final experimental results show that ( Fig.11 ), the modification of Ag-Cu NDs cannot enhance the antifouling performance of GCE but will not affect the antifouling effect of the antifouling interface.
[0105] 5. Take Apt-Ag-Cu NDs / PTMAO-SBMA / GCE and immerse them in 200 μL of 0.01, 0.05, 0.1, 1, 10, 50, and 100 ng mL -1 The working electrode to be detected was then immersed in an electrochemical probe solution and scanned with DPV in the potential range of -0.2V to 0.6V. The corresponding DPV image is shown in Figure 2. Fig.12 The signal inhibition rate was calculated by recording the current signal before and after the detection; the standard curve was obtained based on the signal inhibition rate and the logarithmic value of the chloramphenicol concentration: y = 3.29x + 13.14, (R 2 =0.997, S / N=3), LOD was 0.33 pg mL -1 ( Fig.13 ).
[0106] 6. Take different electrodes of Example 1 and electrodes of Comparative Example 1 to analyze the changes of DPV signals during the gradual construction of the anti-fouling electrochemical sensor. Fig.14 As shown in the figure, when GCE is modified with zwitterionic copolymer (PTMAO-SBMA), the DPV current signal decreases (125.3μA-120.3μA), which is due to the poor conductivity of zwitterionic copolymer, but the modified thickness is thin. Ag-Cu NDs are coated to connect the chloramphenicol aptamer through the Ag-S bond. After modifying apt, the DPV current signal dropped significantly to 88.1μA, which is due to the hindered charge transfer on the electrode surface. It is worth noting that after coating with Ag-Cu NDs, the DPV current response increased from 120.3μA to 127.1μA. It is proved that Ag-Cu NDs can not only be used for the connection of aptamers but also enhance the electrochemical signal. Apt / Ag-Cu NDs / PTMAO-SBMA / GCE was coated at 100.0ng mL -1After incubation in CAP solution for 60 min, the DPV current signal decreased again. This was due to the weak conductivity of the CAP molecule and the conformational change of the chloramphenicol aptamer after binding to the CAP molecule, which caused it to accumulate more densely on the electrode surface, thereby hindering the electron transfer on the electrode surface.
[0107] 7. 100 ng mL -1 of chloramphenicol and 1 μg mL -1 Amoxicillin, ofloxacin, kanamycin, doxycycline and their mixtures were used as detection objects and the prepared antifouling electrochemical aptamer sensor was used for detection. Fig.15 As shown in a, the electrical signal changes in amoxicillin, ofloxacin, kanamycin and doxycycline were very low, 2.7%, 1.3%, 3.5% and 4.1% respectively; while when chloramphenicol and their mixture were detected separately, the signal inhibition rate was 18.2% and 18.9%, indicating that the sensor has excellent selectivity. In addition, the constructed antifouling electrochemical sensor was stored in PBS (10.0 mmol L -1 ) solution, used to detect 100.0ng mL -1 After 5 days of TC, 97.1% of the initial signal was still maintained, indicating that the antifouling electrochemical sensor has good stability ( Fig.15 b). Seven different working electrodes were used for repeatability evaluation. According to step 2.4, three antifouling electrochemical sensors were prepared for each electrode to detect chloramphenicol. The results showed that the proposed antifouling electrochemical aptasensor had excellent repeatability ( Fig.15 c).
[0108] 8. Honey, pork liver and physiological saline were selected as the samples to be tested, and the spike recovery experiment was used to verify the actual application performance of the constructed sensor in the samples to be tested.
[0109] pH 7.4 0.01 mol L -1 Dilute honey to 1% with PBS buffer solution; weigh 3±0.05g of homogenized pig liver sample in a 50ml centrifuge tube, add 3ml of deionized water and shake to mix, then add 6ml of ethyl acetate and shake for 2 minutes, centrifuge at room temperature at 4000 rpm for 10 minutes; take 2ml of the upper liquid and blow dry with nitrogen at 50-60℃. Add 1mL of 0.01mol L -1 Redissolve in PBS buffer solution and centrifuge at room temperature for 5 minutes at 4000 rpm. Take the aqueous phase and dilute it with 1% PBS buffer solution. Prepare 0.9% saline solution with sodium chloride. Add different concentrations of sodium chloride standard solution to the three diluted food samples to ensure that the solution contains 0.5ng mL -1 , 9ng mL -1 and 90.0 ng mL-1 Chloramphenicol was then detected using Apt-Ag-Cu NDs / PTMAO-SBMA / GCE to obtain the spike recovery in the sample. The spiked sample was tested using enzyme-linked immunosorbent assay to verify the results obtained by the constructed sensor to ensure the accuracy of the analysis. The specific results are shown in Table 1 below:
[0110] Table 1
[0111]
[0112]
[0113] It can be seen from Table 1 above that the anti-fouling electrochemical sensor prepared by the present invention can sensitively detect chloramphenicol in the sample to be tested, and this method has broad application prospects in food matrices.
[0114] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A zwitterionic polymer, characterized in that The structural formula of the biomimetic zwitterionic polymer is shown in Formula 1: Wherein, x and y are the numbers of each monomer structural unit.
2. The method for preparing the zwitterionic polymer according to claim 1, characterized in that: The method comprises the following steps: subjecting N-[(3-(dimethylamino)propyl]methacrylamide to an oxidation reaction to obtain a zwitterionic monomer, and subjecting the zwitterionic monomer to a photopolymerization reaction with methacrylate sulfobetaine to obtain the amphoteric polymer.
3. The method for preparing a zwitterionic polymer according to claim 2, characterized in that: The mass ratio of the zwitterionic monomer to methacrylate sulfobetaine is (1-9):
1.
4. An electrochemical sensor, characterized in that The invention comprises an electrode, the surface of the electrode is an antifouling layer formed by the zwitterionic polymer according to claim 1, and the surface of the antifouling layer is loaded with silver-copper nanoparticles and thiol aptamers.
5. The electrochemical sensor according to claim 4, characterized in that The thiol aptamer is a thiol chloramphenicol aptamer.
6. The method for preparing an electrochemical sensor according to any one of claims 4 to 5, characterized in that: The steps include: S1, subjecting N-[(3-(dimethylamino)propyl]methacrylamide to an oxidation reaction to obtain a zwitterionic monomer, mixing the zwitterionic monomer, methacrylate sulfobetaine and a photoinitiator in a solvent to obtain a mixed solution, coating the mixed solution on the surface of an electrode, and then subjecting the mixed solution to a photopolymerization reaction to obtain an electrode 1 having an antifouling layer on the surface; S2, coating a dispersion containing silver-copper nanoparticles on the surface of the anti-fouling layer, reacting to modify the silver-copper nanoparticles on the surface of the anti-fouling layer to obtain electrode 2; placing electrode 2 in a thiol aptamer solution for incubation to obtain the electrochemical sensor.
7. The method for preparing an electrochemical sensor according to claim 6, characterized in that: The silver-copper nanoparticles are synthesized by using silver nanoparticles as a base and adopting a seed growth method.
8. The method for preparing an electrochemical sensor according to claim 6, characterized in that: In step S1, the photopolymerization reaction is carried out under ultraviolet light; and / or the reaction time of the photopolymerization reaction is 20 to 40 minutes.
9. The method for preparing an electrochemical sensor according to claim 6, characterized in that: In step S2, a dispersion containing silver-copper nanoparticles is coated on the surface of the anti-fouling layer, and the dispersion is allowed to stand for a period of time for self-assembly reaction to modify the surface of the anti-fouling layer with silver-copper nanoparticles, thereby obtaining an electrode 2; And / or, the incubation time is 8 to 12 hours; the incubation temperature is 0 to 5°C.
10. Use of the electrochemical sensor according to any one of claims 4 to 5 in detecting chloramphenicol.
Citation Information
Patent Citations
Polydopamine-zwitterionic polymer anti-adhesion coating modification method and application thereof
CN114395059A
Preparation method of bionic mucus antifouling polymer
CN115433324A
Bionic zwitterionic polymer as well as preparation method and application thereof
CN117801163A
Antifouling electrochemical sensor and preparation method and application thereof
CN118533927A
Composite multifunctional coating with electric response characteristic and preparation and application thereof
CN118846257A
Cited By
Preparation method and application of anti-fouling electrochemical sensor
CN121027250A
Preparation method and application of anti-fouling electrochemical sensor
CN121027250B